Mutation Analysis of the LDL Receptor Gene in Indian Families with Familial Hypercholesterolemia - Suyamindra S Kulkarni (Asian Journal of Medical Sciences, 2011)
Objective: Familial Hypercholesterolemia (FH) is a metabolic disorder inherited as an autosomal dominant trait characterized by an increased plasma low-density lipoprotein (LDL) level. The disease is caused by several different mutations in the LDL receptor (LDLR) gene. Several mutations have been reported in this gene in patients from several ethnic groups. Early identification of individuals carrying the defective gene could be useful in reducing the risk of atherosclerosis and myocardial infraction by the available therapeutic methods. The techniques available for determining the number of the functional LDLR molecules are difficult to carry out and expensive. Our study presents mutation analysis of the LDLR gene in 24 Indian families with FH.